(untitled) (Asian Business Research, 2022)
In the course of my country’s economic development, the financial school is not allowed to be ignored. Due to the vigorous development of my country’s economic market in recent years, financial institutions, all major financial institutions, asset management enterprises, and securities companies, etc., are urgently demand for financial majors, and these demands also give financial learning. More challenges from development. Today’s development is closely related to people’s lives and production, but the financial industry has changed a certain change as the economic market changes.